Asymptotic Behavior of Solutions to Abstract Stochastic Fractional Partial Integrodifferential Equations - Zhi-Han Zhao; Yong-Kui Chang; Juan J. Nieto (Abstract and Applied Analysis)
The existence of asymptotically almost automorphic mild solutions to an abstract stochastic fractional partial integrodifferential equation is considered. The main tools are some suitable composition results for asymptotically almost automorphic processes, the theory of sectorial linear operators, and classical fixed point theorems. An example is also given to illustrate the main theorems.